Pasmo Tarczowe pod Wpływem Działania Obciążenia Zewnętrznego - Szelagowski, F. (Engineering Transactions, 1960)
The solution of the problem of an isotropic plate strip subject to the action of a load on the upper and lower edge. The solution reduces, in principle, to the determination of two holomorphic functions D(z) and F(z), figuring in the equations for the stresses X,, X, and Y, (Fig. 1) and the displacements u and U for any point of the region considred.Using the relations between the value of the holomorphic function in the strip region and its real and imaginary part along the edges, the equations (10) and (13) for D(z) and F(z) are derived.